Virtual Reality-Based Visuospatial Training for Older Adults: System Design and Pilot Evaluation of VR RoomSpace - Agatha Maisie Tjandra; Chien-Hsu Chen (Healthcare, 2026)
Background/Objectives: Visuospatial ability supports everyday tasks, such as judging distance and navigating, yet declines with age, especially after 70. This study presents VR RoomSpace, a virtual reality system combining immersive exploration with paper-based tasks to engage allocentric and egocentric spatial frameworks. Methods: Sixty community-dwelling older adults (aged 65–79; M = 69.8, SD = 4.4; MMSE = 29.2, SD = 1.4) trained for eight weeks. The experimental group (n = 31) received four weeks of pen-and-paper training, then four weeks of VR RoomSpace training; the control group (n = 29) received eight weeks of pen-and-paper training. The Mental Rotation Test (MRT; allocentric) and Perspective Taking Spatial Orientation Test (PTSOT; ego-centric) were assessed at baseline and evaluation. Results: Both groups improved from baseline on both measures. Analysis of covariance adjusting for baseline showed no significant between-group difference in the full sample for the MRT (adjusted difference 1.30, 95% CI [−0.31, 2.91], p = 0.113) or the PTSOT (−9.75°, 95% CI [−22.00, 2.51], p = 0.117). An exploratory subgroup analysis favored the experimental group on the MRT among participants aged 70–79 (2.29, 95% CI [0.22, 4.37], p = 0.031, d = 0.91), but this did not survive correction (Holm-adjusted p = 0.251). No differential PTSOT effect emerged in either subgroup. Conclusions: This pilot study shows that VR RoomSpace can be delivered to older adults. While primary outcomes were null, the exploratory analyses suggested a potentially greater allocentric benefit among participants aged 70–79, warranting confirmation in adequately powered studies.